2005
DOI: 10.1093/brain/awh691
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex involvement in chronic analgesic-overuse headache evolving from episodic migraine

Abstract: The way in which medication overuse transforms episodic migraine into chronic daily headache is unknown. To search for candidate brain areas involved in this process, we measured glucose metabolism with 18-FDG PET in 16 chronic migraineurs with analgesic overuse before and 3 weeks after medication withdrawal and compared the data with those of a control population (n = 68). Before withdrawal, the bilateral thalamus, orbitofrontal cortex (OFC), anterior cingulate gyrus, insula/ventral striatum and right inferio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
252
5
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(284 citation statements)
references
References 47 publications
18
252
5
8
Order By: Relevance
“…The partial benefit from detoxification and the severity bias led us to consider this subgroup of chronic-relapsing migraneurs as a separate phenotype, whose features might belong to the substance use disorders spectrum. Recent findings from neuroimaging and neuropsychological studies give strength to this hypothesis [6][7][8]30]. However, this study has a number of limitations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The partial benefit from detoxification and the severity bias led us to consider this subgroup of chronic-relapsing migraneurs as a separate phenotype, whose features might belong to the substance use disorders spectrum. Recent findings from neuroimaging and neuropsychological studies give strength to this hypothesis [6][7][8]30]. However, this study has a number of limitations.…”
Section: Discussionmentioning
confidence: 83%
“…The underlying neurobiology of MO is not well understood. Although it might come from coping with pain and disability associated with migraine, a persistent dysfunction of the orbitofrontal cortex (OFC) and the relative decision-making deficit have been recently reported [6][7][8]. These deficits might explain the above-mentioned maladaptive behaviors and place MO in the substance use disorders spectrum [6].…”
Section: Introductionmentioning
confidence: 99%
“…central pain modulation [133,134] no % of posterior circulation infarcts [104] Medication overuse headache ! metabolism and tissue density orbitofrontal cortex [48,50] ! metabolism/activation of lateral pain system [50,135] %% cortical sensitivity depending on drug overused [49] precuneus connectivity: !…”
Section: Episodic Migraine (Interictal)mentioning
confidence: 99%
“…metabolism and tissue density orbitofrontal cortex [48,50] ! metabolism/activation of lateral pain system [50,135] %% cortical sensitivity depending on drug overused [49] precuneus connectivity: ! with DMN, % with hippocampus [51] % tissue density in PAG [48] Acta Neurol Belg…”
Section: Episodic Migraine (Interictal)mentioning
confidence: 99%
“…Furthermore, a PET study [17] has shown orbitofrontal cortex hypometabolism both in patients with chronic analgesic-overuse headache evolving from episodic migraine, and in patients with drug dependence. Similarly, an fMRI study carried out by our group [18] showed that female patients with chronic migraine with medication overuse (CMwMO) had hypoactivity, compared to controls, in some areas of the lateral pain pathway, primary somatosensory cortex (S1) and posterior parietal cortex (PPC), following noxious mechanical stimuli.…”
mentioning
confidence: 99%